Antenatal diagnosis of myometrial invasion in anterior placenta previa by transabdominal color Doppler ultra sound - Sulaiman, Jwan N. (AL-Kindy College Medical Journal, 2011)
Background: The incidence of maternal mortality in placenta previa accrete is 7%,and its preoperative diagnosis is of a great value. Objective: to evaluate the efficacy of transabdominal color Doppler ultrasound in diagnosing placenta previa accreta and inccreta. Color Doppler imaging criteria used in: includes diffuse parenchymal placental lacunar flow, focal intra parenchymal placental lacunar flow and bladder uterine serosa interphase hyper-vascularity. Design: Prospective study on patients from January2007 to January 2008. Patients and method: 48patients with one caesarean section or more and with persistent anterior placenta previa diagnosed by transabdominal ultrasound were examined by color Doppler at 32 or more weeks of gestation to determine the possibility of myometrial invasion depending on the above color Doppler criteria. Results: Out of 48 patients eleven exhibited characteristic Doppler imaging pattern highly specific for placenta accreta and inccreta according to preceding criteria , one patient had false positive color Doppler imaging result, 5 patients underwent caesarian hysterectomy , the remaining five were treated conservatively by uterine artery ligation and other conservative measures because of bleeding from the lower uterine segment. Conclusion Color Doppler sonography is highly sensitive and specific in the antenatal diagnosis of placenta previa accreta .If a strong suspicion is found before delivery ,appropriate location and timing for delivery should be considered ,to allow access to adequate surgical personel and equipment ,preoperative blood preparation to reduce morbidity and mortality. Journal title Ultrasound in obstetric and gynecology ISSUN 0960- 7692 Source 2000 Vol 15 In 1 PP. 28-35 (22rel)